Information Technology as a Tool to Improve the Quality of American Indian Health Care. - Sequist, Thomas D.; Ayanian, John Z.; Cullen, Theresa (American Journal of Public Health, 2005)
The American Indian/ Alaska Native population experiences a disproportionate burden of disease across a spectrum of conditions. While the recent National Healthcare Disparities Report highlighted differences in quality of care among racial and ethnic groups, there was only very limited information available for American Indians. The Indian Health Service (IHS) is currently enhancing its information systems to improve the measurement of health care quality as well as to support quality improvement initiatives. We summarize current knowledge regarding health care quality for American Indians, highlighting the variation in reported measures in the existing literature. We then discuss how the IHS is using information systems to produce standardized performance measures and present future directions for improving American Indian health care quality.